RECONSTRUCTION OF LAW ENFORCEMENT IN THE PROVISIONS OF ARTICLE 100 OF THE NEW CRIMINAL CODE CONCERNING THE DEATH PENALTY ON PROBATION FROM THE PERSPECTIVE OF VICTIMOLOGY - Ridwan, (Proceeding International Conference on Social Sciences, 2026)
One form of extreme punishment used to deal with serious crimes is the death penalty, which is intended to provide a deterrent effect and protect the community. The history of this punishment shows that, although it has been around for a long time, its success in reducing crime rates is still questionable. Serious cases such as premeditated murder, treason, and extreme violence often involve detention. However, there is no evidence that these arrests are effective in reducing crime, especially corruption and drugs. In addition, human rights, especially the right to life guaranteed by the constitution, and the possibility of irreparable judicial errors after execution, have been a source of criticism. Indonesia uses the "The Indonesian Way" approach in Article 100 of the New Criminal Code, which establishes the death penalty as a last resort after ten years of probation. According to Article 100 (1) of the National Criminal Code, the execution of the death penalty is postponed for 10 (ten) years with two conditions: remorse and desire to repent and improve themselves, as well as the role of the death penalty defendant in the crime. In the National Criminal Code, the death penalty has advantages and disadvantages. The advantage is that the death penalty is regulated as an alternative crime and that execution of the death penalty is delayed, which makes it a middle ground between voters and opponents of the death penalty. The death penalty is the most severe punishment because it is only given to perpetrators of serious crimes such as premeditated murder. Thus, the death penalty shows that the perpetrator is responsible for his actions and has a deterrent effect. Meanwhile, the weakness of Article 110 paragraph (1) of the National Criminal Code is that there is no legal certainty about when the execution of the death penalty will have an impact on the execution of the death penalty pending the probation period. This causes the President's time limit to issue a ruling after considering the Supreme Court's considerations is not clearly regulated, and criminal cases become too long.